The Elusive Republic: Political Economy in Jeffersonian America - McCoy D. R.; McCoy Drew R. (New York London W. W. Norton & Company, 1982)
By investigating eighteenth-century social and economic thought an intellectual world with its own concepts, and assumptions Drew McCoy smoothly integrates the history of ideas and the history of public policy in the Jeffersonian era.
Keywords: 32